Mosquito‐derived ingested DNA as a tool for monitoring terrestrial vertebrates within a peri‐urban environment - Christine Chivas; Adam Stow; Andrew Harford; Thomas J. Mooney; David Loewensteiner; Kate Montgomery; Anthony Chariton (Ecosphere)
Abstract Global biodiversity is declining at an alarming rate. Consequently, there is a pivotal need to determine the occurrences and distributions of threatened species. Monitoring and detection approaches are traditionally reliant on capture (traps and cameras), as well as observations. However, these approaches are time‐consuming and skewed toward the detection of large and/or common species. Invertebrate ingested DNA (iDNA) is being increasingly used as a novel approach for indirectly monitoring terrestrial vertebrates via their DNA in invertebrates with hematophagous, coprophagous, or saprophagous feeding strategies. This study aimed to examine the vertebrate diversity which could be retrieved using mosquito‐derived iDNA in a peri‐urban setting. Furthermore, the study also examined the influence of a human blocking primer and the application of multiple primers on the detection of the targeted taxa. Sampling was performed in Sydney, Australia, in a peri‐urban environment adjacent to both urbanized and protected environments. As a means of ensuring that sampling could be performed by nonscientists, domestically available light traps were used. In total, 118 mosquitoes were captured. DNA was extracted from individual mosquitoes and amplified using four different primers, targeting vertebrates, mammals, and birds, with and without a human blocking primer (except for the bird polymerase chain reactions). The overall diversity retrieved reveals a broad diversity of species with 10 avian taxa and six mammalian taxa, including both native and non‐native species of varying body sizes and behavioral characteristics. Both the multi‐locus approach and the use of a human blocking primer revealed additional diversity. The use of iDNA offers the potential as an important tool for local land managers and citizen science projects for the monitoring of vertebrates.